2007
DOI: 10.3989/revmetalm.2007.v43.i4.72
|View full text |Cite
|
Sign up to set email alerts
|

High temperature fracture mechanisms on non-oriented electrical steels

Abstract: La pérdida de ductilidad a alta temperatura de aceros producidos por colada continua ha sido investigada ampliamente debido a la necesidad de evitar diversas formas de agrietamiento en planchones producidos por colada continua y en cintas fabricadas por laminación en caliente. Este fenómeno ha sido asociado con cambios microestructurales que promueven diversos mecanismos de fragilización: restricción del movimiento de los limites de grano en la austenita [1] , formación de zonas libres de precipitados [2] , fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…1 result about 830 -840 °C. Notably, it predicts lower temperatures than the observed at low ductility values in % RA curves for electrical steels [33] .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…1 result about 830 -840 °C. Notably, it predicts lower temperatures than the observed at low ductility values in % RA curves for electrical steels [33] .…”
Section: Introductionmentioning
confidence: 94%
“…[38] reported that ferrite was formed during the deformation, even above Ae 3, with para-equilibrium, which was analyzed by in-situ X-ray diffraction method. Furthermore, no evidence of formation of ferrite films at austenite grain boundaries was presented in prior work for electrical steels [33] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials employed in the production of this steel include scrap metal 67% and sponge iron 33 %. Big quantities of scrap metal are charged into the electric furnace directly from the container, and therefore, it will result in an increase of residual elements such as Cu and S. These two elements can cause a strong negative effect on the ductility of the steel during hot rolling process [1] .…”
Section: Introductionmentioning
confidence: 99%